A Systematic Review Self-Care Education Program among Type II DM Patients - Muhammad Syikir; Andi Masyitha Irwan; fidya anisa firdaus (Inspirasi Foundation, 2020)
Introduction: The prevalence of Type 2 Diabetes Mellitus was substantially increased around the world, resulting complications and death. Objective: The self-care education program aimed patients to prevent complications and to increase their quality of life is needed. Method: The method used with the help of an electronic data base from journals that have been published through PubMed, Wiley, and Google Scholar as many as 7 articles from 646 articles reviewed. Results: Description of Diabetes Mellitus self-care education program implementation on body biochemical improvement, life quality improvement from physiological, psychological, knowledge, and attitude side. Conclusion: self-care education program that consisted of providing health education to patients and families with a variety of learning methods, training and discussion where patients and families are involved in activities, both in exploring the patient's feelings to goal setting and intervention. Implementation of this self-care education program can be applied to health services with the adjustment of media based on the local conditions.